Determination of antibacterial activity of cinnamon and black cumin extracts, along with MIC\MBC against bacterial isolates and analysis of their phytochemical properties - Moon, Tanha Mollic (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.